A computational study about the types of entropy generation in three different R134a ejector mixing chambers. (March 2016) - Sierra-Pallares, J.; García del Valle, J.; García Carrascal, P.; Castro Ruiz, F.
Highlights: CFD based second law analysis for three ejector geometries. Division of the entropy generation into four basic machanims. Discussion of flow features based on CFD local entropy generation maps. Comparison of the compression mechanisms inside the ejector. Abstract: The purpose of this investigation is to study the efficiency of a R134a ejector operating with three different mixing chambers by means of a CFD based entropy generation analysis. With the aid of the differential equation for entropy, the local entropy generation is pursued. Using this method, the areas where the irreversibilities occur are identified and geometry improvements suggested. The novelty of the numerical procedure presented herein is that the bulk entropy generation is analysed by means of four sources related with viscous dissipation and heat transfer, divided in mean and fluctuating terms. Entropy generation within the boundary layer has also been considered. The latter has proved to be small, as well as the heat transfer contribution. The fluctuating viscous dissipation accounts for more than 75% of the added entropy, being its main sources the shear layer after the nozzle exit and the shock wave trains, independently of their position.